Promotion of organic agriculture through community-based organisations in Quezon Province, Philippines - De Guzman, Rowena P. (Journal of Human Ecology, 2016)
The National Organic Agriculture Program aims to promote organic agriculture (OA) to enhance soil fertility in the Philippines. The success in the promotion of OA is partly dependent on the farmers' organizations (FOs) practicing QA. Using semi-structured interviews, this study describes how five community-based FOs in Quezon Provine facilitate the promotion of OA. The system-structural perspective and contingency theory, were used in analysing the interview data collected. Results showed that since the five FOs are community-based, they are able to address the problems in their respective communities. The successful facilitation of OA can be credited to the formal and centralized set up of the organization, which helped sustain farmer engagement. Moreover, the size of the organizations and the existence of institutional linkages greatly influence the conduct of promotion of OA-related activities. Activities of the organizations increased with bigger membership size and wider linkages. The study lends support to the government efforts to form community-based farmers' organization.